Nutritional Content and Characteristics of Pumpkin Cream Soup with Tempeh Addition as Supplementary Food for Elderly. (17th August 2021) - Setiawan, Budi; Aulia, Salma S.; Sinaga, Tiurma; Sulaeman, Ahmad
Abstract : An increase in the number of elderly people indicates a higher life expectancy. However, this is also a new challenge since the elderly tends to have age-related diseases, thus the physical, psychological, and sensory disorders that will affect their nutritional status. The development of geriatric foods such as cream soup made from pumpkin and tempeh is considered to be the solution to prevent this situation. This study used a factorial randomized design, containing processing methods (fresh and instant) and the addition of tempeh (0%, 75%, and 100%). Sensory evaluation (rating and ranking test), physical characteristics (pH, yield, rehydration, and viscosity), nutritional analysis (proximate, crude fibre, dietary fibre, vitamins B6 and B12, and β -carotene content), and acceptance analysis of cream soup fresh and instant were examined. Physical characterization revealed that the product had a pH of 5.4–5.7, a viscosity of 1250–2190 cP, a rehydration ratio of 5.51–6.47 g mL -1, and a yield of 19.44%–26.9%. The result of sensory evaluation showed that the processing method and tempeh addition had a significant effect (p < 0.05 ) on the product acceptance. This also affects the nutritional value, in which fresh products had higher nutritional value than the instant product, and products with tempeh had higher ash, protein, dietary fibre, and vitamin B12 than products without tempeh. Based on this analysis, the instant cream soup with 75% tempeh is the best formula. In one portion size (50 g), instant cream soup with 75% tempeh met 10% or more of the Indonesian recommended dietary allowance (RDA) for the elderly in terms of protein, carbohydrates, fat, energy, dietary fibre, vitamin B12, vitamin B6, and vitamin A, so it can be recommended as a complementary food for the elderly.